Optimizing ETL Processes for Big Data Applications - Kola, Harish Goud (International Journal of Engineering and Management Research, 2024)
Optimizing large-scale data processing has become crucial in the area of data management due to the constantly growing quantity and complexity of data. Big data analysis involves gathering data in a variety of forms from several sources, cleaning it up, customizing it, and then importing it into a data warehouse. Transformation algorithms are needed to extract data in different forms and convert it to the necessary format. Software programs known as Extraction-Transformation-Loading (ETL) solutions are in charge of extracting data from several sources, cleaning it up, personalizing it, and then putting it into a data warehouse. First, we examine current systems for organizing information and evaluate their advantages and disadvantages in this research. We build a more effective, convenient, and user-friendly big data management platform to address the issues of not being too light, not being timely with data transfer, and not being innovative with data analysis. Because of these experiences, I have a unique perspective on the performance bottlenecks, scalability problems, and extended processing times that often afflict typical ETL operations in the financial services industry. The management of Extract, Transform, Load (ETL) procedures for massive data warehouses has become very difficult due to the growing amount and complexity of data in contemporary businesses. Several optimization methods and approaches for ETL procedures in expansive data warehouse settings are examined in this white paper. It talks about the frameworks, tools, and techniques for streamlining ETL processes, such as distributed computing, data splitting, and parallel processing. The study emphasizes the advantages of efficient ETL operations, including shortened processing times, increased scalability, and better operational efficiency, via an examination of implementation specifics and case studies. Organizations may overcome the drawbacks of conventional ETL operations and gain more agility and competitiveness in the present-day data-driven environment by using sophisticated optimization approaches.